Adalimumab: effective TNF-blockade therapy for ankylosing spondylitis. Issue 5 (October 2007) - Schwab, Pascale; Deodhar, Atul
The armamentarium available for the treatment of ankylosing spondylitis (AS) has for decades been inadequate. The recent introduction of tumor necrosis factor (TNF) antagonists for the treatment of AS has proven pivotal and provided patients with AS an effective treatment option. Indeed both infliximab, a human-mouse chimeric monoclonal antibody directed against TNF, and etanercept, a construct of the Fc portion of the human IgG with soluble receptor of TNF, have demonstrated in clinical trials to improve symptoms of pain and stiffness, physical function, quality of life, as well as MRI inflammation. In 2006, another anti-TNF agent, adalimumab, which is a fully human monoclonal antibody, was approved for the treatment of AS. This report reviews the pharmacologic characteristics of adalimumab as well as its efficacy and safety in AS.